MINIMASI BIAYA BAHAN BAKU KAYU BULAT PADA INDUSTRI PENGGERGAJIAN KAYU JATI DI IPK BRUMBUNG (minimization of round wood raw material cost at teak sawmill at brumbung sawmill) - Hendro Prahasto (Jurnal Penelitian Hasil Hutan, 1993)
The objective of this study is to find optimal allocation of round wood raw material used by teak sawmill, so as to minimize cost of raw materialThe result of linear programming analysis shows that, in 1991 the optimal cost of raw material at Brumbung teak sawmill was Rp 9,992,759,165. Using this optimal raw material allocation scheme, Brumbung teak sawmill could decrease raw material cost about Rp 390,573,835 in 1991.